Prevalence of dental disease in women with breast cancer - Nurova Shoxsanam Norpulatovna (Academia One Publishing, 2024)
In women with breast cancer, in women with early menopause, there is a development of a high level of dental diseases in the adaptation phase of the body, with a lack of the hormone estrogen or its abrupt complete absence after radiation, chemotherapy and hormone therapy. It has also been proven that estrogen deficiency negatively affects the condition of the hard tissues of the tooth and especially the condition of periodontal tissues.
Keywords: Dental defects; periodontal disease; hormones; menopause